Hybrid Solid‐Electrolytes: High Li+ and Na+ Conductivity in New Hybrid Solid Electrolytes based on the Porous MIL‐121 Metal Organic Framework (Adv. Energy Mater. 16/2021). Issue 16 (27th April 2021) - Zettl, Roman; Lunghammer, Sarah; Gadermaier, Bernhard; Boulaoued, Athmane; Johansson, Patrik; Wilkening, H. Martin R.; Hanzu, Ilie
Abstract : In article number 2003542 Martin R. Wilkening, Ilie Hanzu and co‐workers report a new Li + and Na + hybrid solid‐electrolyte which is fabricated via the modification of the MIL‐121 Metal Organic Framework structure, by ion exchange and a soaking electrolyte. A cooperative ion transport mechanism, to which both the porous framework and the small pore‐confined molecules contribute, explains the high ionic conductivity of this solid material.